Pengaruh Kondisi Operasi Alat Pengering Semprot Terhadap Kualitas Susu Bubuk Jagung - Zuhra, Zuhra; Sofyana, Sofyana; Erlina, Cut (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2012)
Drying method is one of techniques used in food preservation. This method usually means reducing water content which is the best contiditon for microorganism growth. Higher water content also causes some enzyms needed for food decomposition cannot work well. This research aims to produce corn milk powder and to study some variables effecting on quality of corn milk powder. Hopefully the results can provide some information and produce good quality of corn milk powder. The drying process was carried out with batch process where the material was put into spray dryer and the process was allowed for the given period of time. Heat was added by direct contact to the material. The pressures of the chamber were 2, 4, 6 and 8 bars and the temperatures were 100, 150, 200 and 250oC. The best results of the research of protein, fat and water contents were 25.86 %, 18.34%, and 6.14%, recpectively.Keywords: atomizer pressure, cornmilk powder, spray dryer, temperature